Antimicrobial activity of extracts of Zingiber officinale and Maclura pomifera on Pseudomona syringae - Ríos Herrera, Erika Natalia; García-Munguía, Alberto Margarito; Hernández-Bautista, Omegar; García-Munguía, Carlos Alberto (Revista Mexicana de Ciencias Agrícolas, 2021)
Bean and tomato in Mexico are two of the products that are an essential part of the diet of the population of this country, they are of great economic, cultural and gastronomic importance. The presence of pests and diseases in crops increases production costs, in addition to the environmental impact and the residuality of pesticides, they can affect human health. The main objective of the research was to study a biocontrol alternative for bacterial diseases, effective, low cost and lower environmental impact. It was developed in the city of Aguascalientes, Mexico in 2019. Natural extracts (ethanol, methanol and water) of Maclura pomifera and Zingiber officinale were produced in raw form by maceration and concentrates by rotary-evaporation, using bases of ethanol, methanol and water. Strains of Pseudomona syringae of pathologies in tomato and green bean were isolated and identified. 14 treatments with three repeats of raw and concentrated extracts were used. Bactericidal activity was evaluated by antibiograms with intervals of 24 h for seven days. Showing the greatest inhibitory effect, the extracts of M. pomifera base ethanol of 100 mg ml-1 and Z. officinale of 100 mg ml-1 base ethanol. For the second test in the decrease in concentrations, the effectiveness of M. pomifera extracts at low concentrations was reiterated, where 10 mg ml-1 was the lowest and most effective concentration in bacterial inhibition. This positions M. pomifera plant extracts as a viable, efficient and economical option in the biocontrol of agricultural bacterial diseases.